FRI0099 Pain reduction is associated with improved work productivity in patients with rheumatoid arthritis. (15th June 2017) - Michaud, K; Zhu, B; Gaich, C; DeLozier, AM; Arora, V; Dickson, C; Smolen, JS
Abstract : Background: Patients with rheumatoid arthritis (RA) indicate pain is an important aspect of disease burden and may persist despite control of disease. In a randomized, double-blind phase 3 clinical trial of baricitinib (RA-BEAM), 1 baricitinib provided significant improvement in pain reduction. It is not clear, however, how much reductions in pain impacted other aspects of life, such as work productivity. Objectives: To assess the relationship between pain reduction and improvements, regardless of treatment, in daily activity and work productivity in patients with RA. Methods: In this post-hoc analysis of RA-BEAM 1, pain for the intention-to-treat patients was assessed using the patient's assessment of pain (0–100 mm visual analogue scale). The Work Productivity and Activity Impairment Questionnaire-RA (WPAI-RA) instrument was used to evaluate the percentage of activity impairment due to RA (impairment in regular daily activities, N=1302), percentage of work-time missed due to RA (absenteeism, N=521), percentage of impairment while working due to RA (presenteeism, N=490), and percentage of overall work impairment due to RA (impairment in work productivity, N=490). Pain was divided into pain reduction groups (<30%, 30% $-<$50%, ≥50% at Weeks 12 and 24; ≥30% [Y/N] and ≥50% [Y/N] at Weeks 1 and 2). Pairwise comparisons on improvement in WPAI-RA scores between pain reduction groups at Weeks 12 and 24 were assessed by ANCOVA adjusting for region, baseline joint erosion status, and baseline values of outcome variables. Missing values were imputed using the modified last-observation carried forward method. Results: At baseline across treatment groups, the mean values ranged from 56–58 for daily activity impairment, 12–13 for absenteeism, 42–46 for presenteeism, and 45–49 for work productivity impairment. A ≥30% reduction in pain as early as Week 1 was associated with significantly greater (p<0.001) improvement than <30% pain reduction in regular daily activity (-22.8 vs -16.0), presenteeism (-17.5 vs. -12.1), and work productivity (-16.8 vs. -11.6) at Week 12. Greater improvement was observed in most WPAI-RA scores in patients who had more pain reduction at Weeks 12 and 24; with a reduction of ≥50% in pain from baseline, the WPAI-RA scores were substantially improved at Weeks 12 or 24 for daily activity, presenteeism, and work productivity (Table). Conclusions: Regardless of treatment, pain reduction was associated with improved regular daily activity and work productivity in patients with RA, with larger levels of reduction related to more improvement. References: Taylor PC, Keystone E, van der Heijde D, et al. Baricitinib Versus Placebo or Adalimumab in Patients with Active Rheumatoid Arthritis (RA) and an Inadequate Response to Background Methotrexate Therapy: Results of a Phase 3 Study. Arthritis Rheum 2015;67(Suppl 10):3928. Disclosure of Interest: K. Michaud Grant/research support from: Pfizer, B. Zhu Employee of: Eli Lilly and Company, C. Gaich Employee of: Eli Lilly and Company, A. DeLozier Employee of: Eli Lilly and Company, V. Arora Employee of: Eli Lilly and Company, C. Dickson Employee of: Eli Lilly and Company, J. Smolen Grant/research support from: Abbvie, Janssen, Lilly, MSD, Pfizer, Roche and has provided expert advice to and/or had speaking engagements for Abbvie, Amgen, Astra-Zeneca, Astro, BMS, Celgene, Celltrion, Chugai, Gilead, Glaxo, ILTOO, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, UCB